The Influence of Local Revenue and Balancing Funds on Capital Expenditure with Economic Growth as an Intervening Variable - Putri, Mezelia Clarinda Laksono; Rahayu, Sri; Olimsar, Fredy (Dinasti Publisher, 2025)
This research employs economic growth as an intervening variable to analyze the impact of local revenue and equalization funds on capital expenditure. It falls under the category of quantitative research and utilizes secondary data sourced from https://jambi.bps.go.id/id and www.djpk.kemenkeu.go.id. The study's population consists of all district and city governments in Jambi Province. However, by applying a saturated sampling technique, 66 data points were selected for analysis. The findings indicate that local revenue positively influences economic growth, while equalization funds have a negative effect on economic growth. Additionally, local revenue does not significantly impact capital expenditure, whereas equalization funds positively influence capital expenditure. Furthermore, economic growth does not affect capital expenditure. The results of the Sobel test, used for hypothesis testing, suggest that economic growth does not mediate the relationship between local revenue and capital expenditure, nor does it mediate the relationship between equalization funds and capital expenditure.